Interactive video mirrors for sports training - Hämäläinen, P. (Proceedings of the third Nordic conference on Human-computer interaction, 2004)
This paper studies gesture and speech controlled video for sports training. The goal is to combine the benefits of recording your performance with video equipment and training with a mirror. For example, a delayed camera view projected on a screen can be used to repeatedly perform and evaluate a spin kick, a move that is difficult to practice with a mirror.